Performance analysis of RIS-assisted mixed RF/THz system - Sai LI; Liang YANG; Qimei CUI; Siyuan YU (Tongxin xuebao)
To solve the problem of the short transmission distance of terahertz (THz) links, the performance of the reconfigurable intelligent surface (RIS)-assisted mixed dual-hop radio frequency (RF)/THz system was studied.An RIS was used to enhance signal strength, thereby improving the system performance.Using the fixed-gain amplify-and-forward protocol, the cumulative distribution function and probability density function of the end-to-end signal-to-noise ratio of the RF/THz link were derived.Capitalizing on the statistical characteristics, the analytical expressions of outage probability, average bit error rate, and average channel capacity of the mixed relaying system were further derived.In addition, the asymptotic analyses of the outage probability and the average bit error rate were carried out to obtain the diversity order of the mixed RF/THz system.Simulation results show that the RIS can effectively improve the performance of the mixed RF/THz system.Furthermore, the system performance is related to the channel fading, pointing errors, and propagation distance.